Contribution of Village Chickens to the Household Income of Resource-Limited Communities - Maswanganye, Miyelani (My University, 2026)
In developing countries, rural households continue to experience poverty and low-income levels, yet almost every household keeps village chickens. Despite the resilience and adaptability of village chickens to harsh environments and low-input requirements, their potential to generate household income remains unquantified and unexplored. The study's broad objective was to examine the contribution of village chickens to household income in resource-limited communities. The specific objectives were to: (1) determine the factors influencing income generation from village chickens and (2) assess the influence of flock size on household income. A mixed‑methods approach was employed, combining household surveys, focus group discussions, and household observations to generate quantitative and qualitative insights. Eighteen focus group discussions (FGDs) were held. In addition, a purposive sampling technique was used to administer a structured questionnaire to 150 households in the Musina Local Municipality. Quantitative data were analysed using the Statistical Package for the Social Sciences (SPSS) version 28, while qualitative data were analysed through thematic content analysis using ATLAS. ti. version 8. The findings revealed that households primarily kept village chickens for meat, highlighting their role in food and nutrition security, while income generation was a secondary but meaningful function. Gender, education, and employment status did not influence chicken sales (P > 0.05). However, flock size (χ2 =18.685; OR = 4.52), livestock training (χ2 = 4.929), and membership in farmer associations (χ2 = 10.894) increased the likelihood of selling village chickens (P > 0.05). The common selling price for chicken ranged from USD 5.79 to USD 6.31. The effects of educational level, chicken ownership, and flock size on price per unit were significant (P < 0.05). Income from chickens was positively related to production potential (ρ = 0.212; P < 0.05) and flock size (ρ = 0.260; P < 0.01). There was an association between chicken sales and food security (P < 0.001). Housing quality conditions, including shelter type (χ² = 9.74), Nesting area (χ² = 34.85), roosting area (χ² = 8.79), and predation control (χ² = 24.21), influenced flock size (P < 0.05). Supplementary feeding (χ² = 10.73), proportion of feeds (χ² = 26.72), vaccination (χ² = 27.43), disease control (χ² = 11.24), and mortality recording (χ² = 5.12) also influenced flock size (P < 0.05). Socio-economic demographics, including livestock training (χ² = 23.45; RO = 1.24), membership of a farmers' association (χ² = 4.05; RO = 1.61), and employment status (χ² = 5.12), were associated with flock size (P < 0.05). Larger flocks were strongly associated with higher sales and income, particularly during the festive (Y = 7.93x + 7.68; P < 0.05) with each additional bird associated with about USD 7.93 and harvesting (Y = 11.60x + 6.0; P < 0.05) periods, with an addition of and USD 11.60, respectively. confirming that flock size is a key asset enabling market participation. Despite this income from chickens remained modest (USD 75 per household per year), constrained by slow growth rates, limited markets, pricing inconsistencies, and high mortality. It was concluded that increasing village chicken flock sizes greatly enhances household income, food security and rural livelihoods. Efforts to increase flock size, therefore, need to be strengthened.
AGMARD
Institute for Rural Development
Keywords: Livelihoods; Poverty; UCTD; Resilience; Supplementary feeding; Village chickens; 338.47664930968257; Chickens -- South Africa -- Limpopo; Poultry -- South Africa -- Limpopo; Rural families -- South Africa -- Limpopo; Villages -- South Africa -- Limpopo; Household -- Economic conditions -- South Africa -- Limpopo